2009
DOI: 10.3727/096504009788428479
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Selenite Induces Apoptosis in Acute Promyelocytic Leukemia-Derived NB4 Cells Through Mitochondria-Dependent Pathway

Abstract: Our previous study has shown that sodium selenite can cause apoptosis in acute promyelocytic leukemia-derived NB4 cells in a caspase-dependent manner involving Deltapsim disruption and cleavage of Bcl-2, but more detailed mechanism(s) remain unclear. Here we showed that mitochondrial apoptosis signaling pathway played a vital role in apoptosis induced by sodium selenite based on the following findings: 1) cytochrome c release, activation of caspase 9, mitochondrial targeting, and oligermerization of Bax; 2) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Bcl-2 family proteins are essential regulators of selenite-induced apoptosis [23][24][25]. The cells were exposed to 10 μM selenite for 24 h, and co-immunoprecipitation was used to detect the interactions between PKD1 and CREB.…”
Section: Selenite Suppresses Creb Phosphorylation and Subsequently Rementioning
confidence: 99%
“…Bcl-2 family proteins are essential regulators of selenite-induced apoptosis [23][24][25]. The cells were exposed to 10 μM selenite for 24 h, and co-immunoprecipitation was used to detect the interactions between PKD1 and CREB.…”
Section: Selenite Suppresses Creb Phosphorylation and Subsequently Rementioning
confidence: 99%
“…Also, TUNEL test in AGS cells treated with 10 μM of apoptosis activator 2/ml of RPMI 1640 culture media supplemented with 1% of BSA showed a significant increase in apoptosis in comparison with non-treated AGS cells and selenite sodium control concentration (2.5 and 4 mM) which causes necrosis instead of apoptosis as seen in AGS cells[23] [Figure 2]. …”
Section: Resultsmentioning
confidence: 99%
“…Analysis of apoptosis by Quantify Nucleosomes in cell cultures with the cell death detection ELISA showed that AGS cells treated with 10 μM of apoptosis activate 2/ml of RPMI 1640 culture media supplemented with 1% of BSA showed a significant increase in apoptosis in comparison with non-treated AGS cells. Also, in this experiment, cytotoxic concentrations (2.5 and 4 mM) of selenite sodium were used as control of cell death by necrosis[23] [Figure 3]. …”
Section: Resultsmentioning
confidence: 99%
“…These results, along with those obtained from selenite release profiles in PBS solution (Figure ), indicated that HANSe3 materials could be degraded in the tumor tissue and then release selenite ions, which further inhibited tumor growth. Indeed, selenite ions could inhibit cancer cell growth by inducing apoptosis …”
Section: Methodsmentioning
confidence: 99%